Pemikiran Fikih Kontemporer Muhammad Syahrur tentang Poligami dan Jilbab - Mustaqim, Abdul (Al-Manahij: Jurnal Kajian Hukum Islam, 2011)
One fresh contribution to the contemporary study of fiqh (Islamic jurisprudence) is the theory of limits (nazariyyah al-hudud) promoted by a Syirian liberal Islamic figure, Muhammad Syahrur. Syahrurâ€™s theory of limits solves the epistemological deadlock of previous works. Syahrur asserts that the theory of limits is an approach within ijtihad (individual interpretation) to study the muhkamat verses (clear and direct verses of law) of the Qurâ€™an. The term â€œlimitâ€ (hudud) used by Syahrur refers to the meaning of â€œthe bounds or restrictions of God which should not be violated, contained in the dynamic, flexible, and elastic domain of ijtihad. By using the theory of limit, Syahrur tries to re-constructs both concept poligamy and jilbab as contribution to the contemporary study of Islamic jurisprudence.